Influence of experimental pain on the spatio-temporal activity of upper trapezius during dynamic lifting – An investigation using Bayesian spatio-temporal ANOVA. (October 2019) - Liew, Bernard X.W.; (Ryan) Yue, Yu; Cescon, Corrado; Barbero, Marco; Falla, Deborah
Abstract: High-density surface electromyography (HDsEMG) provides a detailed analysis of a muscle's spatial distribution of activity. We applied a Bayesian spatio-temporal statistical method to quantify how acute nociception and task repetition alters the upper trapezius instantaneous spatial distribution of activity during dynamic muscular contractions. Ten male adults performed repeated lifting of a 1 kg box between shelves positioned at hip and shoulder heights with a cycle time of 3 s for 50 cycles under four conditions: baseline, isotonic and hypertonic saline injections (nociception) to the right upper trapezius, and 15 min post injection. Activity of the right upper trapezius was measured using a 64-channel surface electrode grid. Statistical inference was performed using Integrated Nested Laplace Approximations (INLA), and significance was determined by a non-zero crossing of the Bayesian 95% credible intervals (CrI). The maximal decrease in activity after nociception was −38.1 µV [95% CrI −40.9 to −35.3] at 30% of the lift cycle when compared to baseline. The maximal reduction in muscle activity between the early and later phases of lifting in the presence of nociception was by 10.4 µV [95% CrI 8.2–12.6]. A more holistic understanding of muscle behaviour is achieved using spatio-temporal inference than traditional reductionist methods.